2020
DOI: 10.24839/2325-7342.jn25.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Model Minority Myth Salience on White Americans’ Perceptions of Black Americans and Their Support for Affirmative Action

Abstract: ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929. Its mission: "recognizing and promoting excellence in the science and application of psy chol ogy." Mem ber ship is open to undergraduates, graduate students, faculty, and alumni mak ing the study of psy chol ogy one of their major interests and who meet Psi Chi's min i mum qual i fi ca tions. Psi Chi is a member of the As so cia tion of Col lege Honor So ci et ies (ACHS), and is an affiliate of the Ameri can Psy cho lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Although research has highlighted the detrimental consequences of these stereotypes on Asian American mental health (Noh, 2018; Tummala-Narra et al, 2018), scholars have critiqued the lack of attention paid to white supremacy as the motivation behind the model minority myth (MMM; Poon et al, 2016; Yu, 2006). In our literature review, we also found little scholarship explicitly linking anti-Asian racism with antiblackness (Lee & Outten, 2020; Liu, 2018; Yi & Todd, 2021). Given that Asian Americans are positioned in the role of “middleman minority” (Wu, 2002, p. 58), as a buffer and a more acceptable minority than Black Americans, we believed that it was critical to acknowledge antiblackness as an inherent assumption in Asian American experiences of racial triangulation.…”
Section: The Racial Positionality Of Asian Americans and Antiblacknessmentioning
confidence: 86%
See 1 more Smart Citation
“…Although research has highlighted the detrimental consequences of these stereotypes on Asian American mental health (Noh, 2018; Tummala-Narra et al, 2018), scholars have critiqued the lack of attention paid to white supremacy as the motivation behind the model minority myth (MMM; Poon et al, 2016; Yu, 2006). In our literature review, we also found little scholarship explicitly linking anti-Asian racism with antiblackness (Lee & Outten, 2020; Liu, 2018; Yi & Todd, 2021). Given that Asian Americans are positioned in the role of “middleman minority” (Wu, 2002, p. 58), as a buffer and a more acceptable minority than Black Americans, we believed that it was critical to acknowledge antiblackness as an inherent assumption in Asian American experiences of racial triangulation.…”
Section: The Racial Positionality Of Asian Americans and Antiblacknessmentioning
confidence: 86%
“…While there is a growing body of empirical research on racial triangulation and the MMM (Chan, 2019; Yi & Todd, 2021), few studies simultaneously examine antiblackness. Recent scholarship has highlighted the link between the endorsement of the MMM and anti-Black attitudes in Asian Americans (Yi & Todd, 2021) and White Americans (Lee & Outten, 2020). However, this work has not captured the interplay of antiblackness and anti-Asian racism.…”
Section: The Racial Positionality Of Asian Americans and Antiblacknessmentioning
confidence: 99%
“…We suggest that guidance counselors at institutions with lower SES and higher prestige may be particularly sensitive to the maintenance of Whiteness in STEM fields. The widespread acceptance of the Model Minority Myth (Lee & Outten, 2020) and Asian Americans as an overrepresented ethnic-racial group in STEM participation (NSF, 2017) reinforce that Asian Americans are a threat to White students in STEM. Indeed, research has highlighted the notion of "Asian threat" in relation to school SES and STEM prestige.…”
Section: Discussionmentioning
confidence: 99%
“…In education, this has resulted in the unique and harmful stereotyping of Black and Latinx students as unintelligent and lacking motivation. In contrast, Asian students are stereotyped using the Model Minority , the myth of universal intelligence (Lee & Outten, 2020). This myth heightens the threat Asian Americans pose to Whites’ maintenance of supremacy.…”
Section: The Present Studymentioning
confidence: 99%
“…Social science has established that the MMM and PFS can be detrimental to the well‐being of Asian Americans and have negative implications for U.S. race relations (Chan & Mendoza‐Denton, 2008; Huynh et al., 2011; Iwamoto & Liu, 2010; Kim et al., 2011; Lee & Outten, 2020). However, there is a lack of research examining whether racial microaggressions that Asian Americans face such as the MMM—whether expressed ambiguously or unambiguously—are perceived as racist by laypeople (see Alt et al., 2019, for an example).…”
Section: Racial Microaggressions: the Model Minority Myth And Perpetu...mentioning
confidence: 99%